2019
DOI: 10.1186/s12885-019-6170-7
|View full text |Cite
|
Sign up to set email alerts
|

Trained facilitators’ experiences with structured advance care planning conversations in oncology: an international focus group study within the ACTION trial

Abstract: BackgroundIn oncology, Health Care Professionals often experience conducting Advance Care Planning (ACP) conversations as difficult and are hesitant to start them. A structured approach could help to overcome this. In the ACTION trial, a Phase III multi-center cluster-randomized clinical trial in six European countries (Belgium, Denmark, Italy, the Netherlands, Slovenia, United Kingdom), patients with advanced lung or colorectal cancer are invited to have one or two structured ACP conversations with a trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Palliative care patients can find it difficult to raise how they are feeling about their illness (Momen et al., 2012) and expect practitioners who are looking after them to initiate the conversation (Almack et al., 2012). In this study, practitioners found using a conversational guide a positive as well as a challenging experience and similar experiences were reported in a recent advance care planning study (Zwakman et al., 2019). As indicated in our findings, the importance of training, learning by experience and having the opportunity to take part in reflective discussions was seen to increase practitioner self‐confidence (Zwakman et al., 2019).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Palliative care patients can find it difficult to raise how they are feeling about their illness (Momen et al., 2012) and expect practitioners who are looking after them to initiate the conversation (Almack et al., 2012). In this study, practitioners found using a conversational guide a positive as well as a challenging experience and similar experiences were reported in a recent advance care planning study (Zwakman et al., 2019). As indicated in our findings, the importance of training, learning by experience and having the opportunity to take part in reflective discussions was seen to increase practitioner self‐confidence (Zwakman et al., 2019).…”
Section: Discussionsupporting
confidence: 82%
“…In this study, practitioners found using a conversational guide a positive as well as a challenging experience and similar experiences were reported in a recent advance care planning study (Zwakman et al., 2019). As indicated in our findings, the importance of training, learning by experience and having the opportunity to take part in reflective discussions was seen to increase practitioner self‐confidence (Zwakman et al., 2019). The importance of being attuned to palliative care patients and family carers levels of understanding and readiness (Etkind, Bristowe, Bailey, Selman, & Murtagh, 2017) especially when using a conversational guide (Zwakman et al., 2019), such as the Attitude to Health Change scales, needs to be recognised.…”
Section: Discussionsupporting
confidence: 82%
“…ACP involves ongoing conversations between healthcare professionals, patients, and the patients' loved ones. The objective of these conversations is to communicate to the healthcare team the patients' wishes, values, beliefs, and goals for long-term, future medical treatment and care in advance of a medical crisis (1). Unfortunately, patients are not always receptive to these conversations and are often more focused on a cure and escalation of treatment options.…”
Section: Case Studymentioning
confidence: 99%
“…Studies have shown that ICU nurses are at high risk for moral distress due to advances in life-support technology, the intense pace of the work environment, and the constant exposure to death (5). These factors have been shown to increase the number of reported cases of moral distress among ICU nurses and related healthcare professionals (1).…”
Section: Case Studymentioning
confidence: 99%